Spider-Man : into the Spider-Verse [videorecording (Blu-Ray + DVD)] - Rothman, Rodney; Lord, Phil, 1977-; Pemberton, Daniel (Sony Pictures Home Entertainment, 2019)
When Miles Morales, a teenager living in New York, becomes the new Spider-Man, he must team up with Spider-Man counterparts from other dimensions to save New York City from Kingpin.